Analysis of the Compliance Level of Micro, Small and Medium Enterprises Taxpayers after the implementation of Government Regulation Number 23 of 2018 - Trisnanty Isna Edy; Lia Dama Yanti; Rina Aprilyanti; Suhendar Janamarta (Komunitas Dosen Indonesia, 2021)
Tax has an important role in realizing government programs for the welfare of the people, for this reason the government tries to encourage potential compliance of taxpayers for Micro, Small and Medium Enterprises to increase the amount of regional income through various policies issued by the Directorate General of Taxes so that tax revenue targets can be achieved. This study aims to determine the level of taxpayer compliance of Micro, Small and Medium Enterprises with the independent variables used are knowledge of taxation, understanding of tax regulations and awareness of taxpayers. The research sample was using purposive sampling technique taken and obtained as many as 67 respondents who were used as samples. The data analysis technique used classical assumption test, hypothesis test and data analysis. The results of data processing showed variable tax knowledge has a value of t count 2,034> 1,998 t table, variable understanding of tax laws has value t 2,293> 1,998 t table and taxpayer awareness variable has a value of t count 2,084> 1,998 t table F test simultaneous test results on the significant value of 0.000> 0.05 with f value count 28 299> 2.75 f table so that we can conclude the independent variables jointly significant effect on tax compliance